Calificación de la estufa Ecocell 55L (Estufa N° 5) ubicada en el área de microbiología del departamento de control de calidad de Laboratorios farmacéuticos Markos S. A. - Floreano Mercedes, Katherine Jhovana (2015)
A cross-sectional retrospective study, on the qualification of installation, operation and performance of the stove Ecocell 55L (Stove Nª5) located in the Department of Microbiology Department of Quality Control of Pharmaceutical Laboratories Markos S.A. stove 55L Ecocell plays a very important role during sterilization of equipment used in the area of microbiology, the total destruction of viable microorganisms present in a given material, in order not to affect the results for products pharmaceuticals. The study established protocols and technical reports for the team, where the requirements and specifications that must be met for use are stressed. The final results were as opinions Qualification Installation, Operation and Performance, that the equipment is suitable for its intended use.